KFC=kma

Simple and best practice solution for KFC=kma equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for KFC=kma equation:


Simplifying
KFC = kma

Solving
CFK = akm

Solving for variable 'C'.

Move all terms containing C to the left, all other terms to the right.

Divide each side by 'FK'.
C = akmF-1K-1

Simplifying
C = akmF-1K-1

See similar equations:

| logx+log(x+1)=12 | | d-67=33 | | 3x+x+96=180 | | 2p-qr= | | u=6(9n+31)+7(n+1) | | 40-5d=18d | | 314+2=350 | | 0.50x=55+(x-70)0.33 | | x+11x+24=0 | | 5-2(x+5)=39 | | 20x+30=14x+6 | | 50.45m+60=57.95m | | t^4+43t+42=0 | | 466/20= | | 4.37(4s)+3.43s=62.73 | | 5x+3(5x-18)=108 | | 9(6x-8)=26 | | p^3-1p=0 | | 6(4x-8)=20 | | 1x*5=49 | | 12=m-(-6) | | 8-6=-8 | | 1.1z+-3.3=-8.8 | | 4y-18=6 | | 7(x-8)=35 | | A=2(x)(x)(x)+3(x)(x)+6 | | x^2+21x+10=0 | | 0.15(c+9)=0.9 | | x^5-2x^3-4x=0 | | -0.85(n+3)=3.4 | | -7y+14=-21 | | 6x-(11)-(7x)+12= |

Equations solver categories